Caseous Necrosis of Mitral Annulus: A Rare Cause of Stroke. (12th May 2013) - Corre, Jérôme; Leroux, Lionel; Coste, Pierre
Abstract : The current report describes a rare case of a caseous necrosis presenting as a pseudotumor in ventricle, revealed by stroke. Cerebral MRI, showing multiples lacunes, evocates a cardioembolic mechanism. Transthoracic and transesophageal echocardiography demonstrate a large hyperechogenic mass fixed to the posterior mitral valve and annulus while thoracic tomography revealed a fully calcified lesion, at the mitral annulus, evocative of caseus necrosis. Medical therapy was preferred (anticoagulation), because of her age and the decaying nature of surgery.